Physicochemical, mechanical and electrical properties of epoxy-based syntactic foam under thermal and hydrothermal aging conditions. (December 2022) - Li, Le; Dai, Xiaohan; Li, Yanda; Zhou, Songsong; Liu, Hechen; Ma, Yunfan; Zhang, Zhongyuan; Liu, Yunpeng
Abstract: In this study, epoxy resin containing hollow polymeric microspheres as an insulating material was synthesized and subjected to thermal and hydrothermal aging. Scanning electron microscopy (SEM) and three-dimensional computed tomography (3D CT) were used to examine the internal structures of the specimens as they aged. Thermogravimetric analysis (TGA) and Fourier transform infrared spectra (FT-IR) helped to elucidate the physical and chemical changes associated with aging. Tensile, flexural, dynamic mechanical analysis (DMA), and other mechanical tests were used to examine the mechanical properties of the syntactic foams (SFs) as they aged. Electrical tests such as the leakage current and breakdown strength were used to measure how effectively the SF materials maintained their insulating characteristics with aging. By comparing the aged and unaged specimens, the aging mechanism of the SF was elucidated. The findings demonstrated that the epoxy resin matrix composite foam packed with hollow polymeric microspheres had little effect on thermal aging and exhibited good hydrothermal aging resistance. The microstructures of the specimens subjected to thermal aging barely changed; however, hydrothermal aging resulted in dramatic changes. Notably, the comprehensive properties of the SF increased during thermal aging and hydrothermal aging, possibly due to an increase in secondary crosslinking density after a certain period of aging. The thermal and hydrothermal aging specimens had maximum tensile strengths of 14 and 13 MPa, respectively. The tensile strength dropped as aging time increased to 11.6 and 7 MPa, respectively. Furthermore, while the breakdown strengths of the hydrothermal samples continued to fall, the breakdown strengths of the thermal specimens initially increased and subsequently decreased, with a maximum value of 40.76 kV/mm. This was possibly related to the fact that the crosslinking reaction dominated the thermal aging process, whereas hydrothermal aging had numerous implications on the characteristics of the SF materials. This study showed that the SF filled with hollow polymeric microspheres had the potential for long-term durability in hot and humid environments, supporting its application as an insulation material in composite insulation cores. Graphical Abstract: ga1 Highlights: The aging-time related micromorphology, physicochemical, mechanical and electrical performance of SF are investigated. Compared with thermal aging, hydrothermal aging exhibits a more serious threat to the overall performance. The trend of water absorption of epoxy resin-based syntactic foam shows non-Fick law. The results of three-dimensional computed tomography reveal that aging increase the number and length of pores.